National Medical Expenditure Survey, 1987: Household Survey, Health Status Questionnaire and Access to Care Supplement (Public Use Tape 9) ([Verlag nicht ermittelbar], 1992)
Public Use Tape 9 contains the initial release of data from two supplementary parts of the 1987 National Medical Expenditure Survey's Household Survey: the Health Status Questionnaire, and the Access to Care Supplement. The file provides person-level data for all those respondents (other than infants less than one year of age) with both information for their entire period of 1987 survey eligibility (Rounds 1-4) and valid data on a minimum set of items in both the Health Status Questionnaire and Access to Care Supplement. The minimum items were: perceived general health status, at least one question on availability and characteristics of a usual source of medical or dental care, all items in the checklists of chronic conditions (for adults aged 18 and over), at least one question on screening for breast and cervical cancer (for adult females), and all questions on immunizations (for children aged 1-17). The Health Status Questionnaire was administered in three age-specific versions between Rounds 1 and 2 of the interviews. Adults aged 18 and over responded for themselves and for children aged 5-17 and under 5 years in their families. The Questionnaire contained items concerning self-assessments of current and past health status, acute and chronic conditions, vision and hearing, dental status, mental health and functional ability, and health-related behaviors such as care-seeking and preventive care. The Access to Care Supplement was administered to all eligible household respondents during Round 3 interviews, and covered access to and usual sources of medical and dental care. For medical providers identified as a usual source of care, information was sought on their specialty, sex, race/ethnicity, and on availability and convenience in terms of hours of practice, travel and waiting times, and related items. Other topics in the Access to Care Supplement included reasons for the lack of a usual source of care and sources of care during an illness. The file also includes basic demographic data from the Household Survey.